Optimización de portafolios de activos de renta fija en Colombia (2020)
In the following research, a tool for the optimization of a portfolio of fixed income assets will be presented, quantifying market risk using DV01 and duration as a risk measure. The objective of this research is to implement linear programming to portfolio theory. This application is intended to be very useful for an investor client or provisional investor with the following functions: add bonds, obtain an expected return at the lowest possible level of risk, be able to keep track of the losses and gains of your portfolio, modify prices of bonds, eliminate bonds, quantify market risk through DV01 and modified duration. The above will be developed using knowledge in linear optimization, corporate finance, portfolio risk management and the use of the R Studio computational tool. The work will be divided into three sections. In the first section the theory will be developed, which includes everything corresponding to fixed income assets, the relevant linear optimization knowledge to achieve the operation of the application and a global vision of the Colombian market. Next, the problem will be announced, together with the motivation to carry out this investigation, the affected agents and the relevant aspects so that this is a solution within the Colombian context. Finally, the functioning of the tool, information inputs and outputs, the system of linear restrictions implemented in it, the results and conclusions of the research will be announced.